Comparing Building Information Modeling Skills of Project Managers and BIM Managers Based on Social Media Analysis. (2016) - Rahman, Rahimi A.; Alsafouri, Suleiman; Tang, Pingbo; Ayer, Steven K.
Abstract: Building Information Modeling (BIM) education may accelerate the process of adopting BIM in construction projects. The education community has been examining the best ways of introducing BIM into the curricula. However, individuals in different positions, such as project managers and BIM managers, may require different BIM skills in practice. Thus, understanding BIM skills could help to better formulate the education program for college students and industry professionals. The authors explored this topic by addressing two research questions: 1) What are the BIM skills possessed by individuals that increase the likelihood of having the titles "project manager" and "BIM manager"? 2) How do these skill-sets differ between project managers and BIM managers? These questions are addressed through an analysis of the LinkedIn profiles of architecture, engineering, construction, and operations (AECO) professionals. Data collection involved gathering endorsed skills, number of endorsements, current position, past positions, and years of work experiences from LinkedIn profiles of AECO professionals. This article identified BIM skills and other skills correlated with BIM skills that increase the likelihood of an individual to own the titles of "project manager" and "BIM manager." This analysis showed that the number of skills shared between project managers and BIM managers were greater than the number of unique skills possessed by either position. While the two positions shared certain skills, subsequent analysis suggested that many of those skills were correlated with different skills. This may suggest that, while there is overlap in the skills possessed between individuals in each position, the way in which they use those skillsets may differ.